Navigating diabetes care inequities: an observational study linking chronic care model’s structural elements to process and outcomes of type 2 diabetes care in Belgium - Philippe Bos; Katrien Danhieux; Edwin Wouters; Josefien van Olmen; Veerle Buffel (International Journal for Equity in Health)
Abstract Background Although the Chronic Care Model (CCM) provides the essential structural components of practice organisation to deliver high-quality type 2 diabetes (T2D) care, little is known about which of its elements are most important, and the extent to which it may reduce social inequities in the quality of T2D care. This study aims to assess the association between the implementation of CCM’s structural elements and the quality of T2D care processes and outcomes in Flanders (Belgium), paying specific attention to differences by patients’ socioeconomic vulnerability. Methods We developed a longitudinal database combining information on primary care practices’ CCM implementation, with individual-level health insurance and medical lab data. Our sample included 7,593 T2D patients aged 40 years and above from 58 primary care practices in Flanders, followed up from 2017 to 2019. Medical lab data were available for a subsample of 4,549 patients. By estimating a series of hierarchical mixed-effects models, we assessed the association between primary care practices’ CCM implementation and two process and two outcome indicators of T2D care. In addition, we explored cross-level interactions with patients’ socioeconomic vulnerability. Results Patients were more likely to have their HbA1c tested twice a year and LDL cholesterol tested yearly in practices with a higher overall CCM implementation. Regarding the different CCM elements, the clinical information system and linkages to the community were significantly associated with higher odds of being up-to-date with HbA1c testing, whereas stronger community linkages was the only dimension significantly associated with yearly LDL cholesterol testing. While socioeconomic vulnerable patients were less likely to have their HbA1c tested twice yearly, this difference disappeared in the highest-scoring practices. Regarding the outcome indicators, only a negligible proportion of variation in HbA1c and LDL cholesterol levels was due to systematic differences between practices, and hence, no clinically relevant associations with the CCM elements were found. Conclusion Our pioneering findings support the social capital pathway, as CCM implementation is associated with a reduction in the healthcare inequity gap in the T2D care process. This suggests that promoting CCM implementation may improve healthcare equity, particularly in regions with significant socioeconomic disparities or high concentrations of deprived individuals.